Effect of direct and indirect teacher feedback on accuracy of English writing: a quasi-experimental study among Pakistani undergraduate students - Nusrat, Aasia; Ashraf, Farzana; Narcy-Combes, Marie Francoise (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introducing new techniques to improve learner-teacher interaction receives substantial attention from the field of educational psychology. The current research aims to investigate the effect of teacher feedback on the written English accuracy of English as Second Language (ESL) students. In a quasi-experimental study, 90 participants were given three distinct forms of feedback (i.e. oral meta-linguistic, also called direct feedback; written indirect feedback and no feedback) for writing errors of three types (i.e. verb tenses, use of articles and prepositions) and were assessed three times during the study (i.e., pre-test, immediate post-test and delayed test). One-way ANOVA demonstrated that the ESL learners given direct meta-linguistic oral feedback reported fewer errors in two out of the three linguistic forms in subsequent writing in comparison with ESL learners who received indirect written feedback and those who did not receive feedback. Findings suggest that introducing oral meta-linguistic teacher feedback in the Pakistani language learning context can improve the English language learning of students.